Fungicide application at anthesis of wheat provides effective control of leaf spotting diseases in western Canada. (October 2018) - MacLean, D.E.; Lobo, J.M.; Coles, K.; Harding, M.W.; May, W.E.; Peng, G.; Turkington, T.K.; Kutcher, H.R.
Abstract: Leaf spotting diseases commonly occur on spring wheat crops grown in Saskatchewan, causing yield losses of up to 15%, although greater losses have been documented during severe epidemics. In the past decade, Fusarium head blight (FHB) has become a major concern for growers resulting in extensive use of fungicide to mitigate the disease. The optimal fungicide timing for leaf spot control is generally at the flag-leaf stage, while the optimal timing for FHB is during anthesis. The objective of this study was to determine whether applying fungicide at anthesis timing can provide adequate control of leaf spots when compared to application at flag-leaf stage. Fungicide treatments applied at flag-leaf, anthesis, and both growth stages were evaluated on the cv. Carberry. Prothioconazole + tebuconazole and tebuconazole (only) applied at anthesis provided adequate control of leaf spots, although the severity of leaf diseases was slightly higher in this treatment than application at flag-leaf stage but yields were similar. Test weight and thousand kernel weight were improved with the application at anthesis relative to that at flag-leaf stage. Two applications of fungicide provided only a small incremental benefit to the anthesis application, and would not be economically justified in western Canada at this time. Anthesis fungicide application provided adequate leaf spot disease control and is the optimum timing for the control of FHB. Highlights: Fungicide application at anthesis and at flag leaf stages to control leaf spots resulted in similar yield. Fungicide application at anthesis improved test weigh and thousand kernel weight compared to application at flag leaf stage. Fungicide applications at both anthesis and flag leaf stages resulted in marginal yield increase. The biological fungicide had no effect on any of the seed quality factors measured.